ANALISIS PENGARUH PEMASARAN DIGITAL (DIGITAL MARKETING) TERHADAP BRAND AWARENESS PADA E-COMMERCE - Yacub, Rudi; Mustajab, Wahyu (Manajerial : Jurnal Manajemen dan Sistem Informasi, 2020)
This study aims to determine whether there is an effect of digital marketing (digital marketing on brand awareness), while the independent variables are Twitter (X1), Instagram (X2) and Facebook (X3) and the dependent variable is brand Awarness (Y). using multiple linear analysis techniques.For data collection researchers used an online questionnaire via Google form.The results of the data processed showed that digital marketing variables using Instagram and Facebook had a significant influence on brand awareness, namely with a tcount of 19,580 and significance of 0,000 so that H1 was insulted (X2 ).